Prohemostatic Interventions in Trauma: Resuscitation-Associated Coagulopathy, Acute Traumatic Coagulopathy, Hemostatic Resuscitation, and Other Hemostatic Interventions - Howard, Benjamin M.; Daley, Aaron T.; Cohen, Mitchell Jay (Seminars in Thrombosis and Hemostasis, 2012)
Trauma is the most common cause of death in the young and hemorrhage is the most important cause of death in patients with trauma. Recently redefined pathways of inflammation and coagulation, together with hypothermia and acidosis contribute to trauma-associated coagulopathy and aggravation of bleeding. Pharmacological prohemostatic agents may be useful to (partly) correct the coagulopathy in trauma patients and may serve as useful adjunctive treatment options in patients with severe blood loss after trauma. Recombinant factor VIIa, fibrinogen and prothrombin complex concentrates, and antifibrinolytic agents have been evaluated in clinical trials. These interventions show promising effects but their efficacy in reducing clinically important outcome parameters need to be confirmed in clinical studies.
Keywords: trauma; coagulopathy; acute traumatic coagulopathy; hemostatic resuscitation; hemostatic interventions